Malory’s ‘Vertuouse Love’ as metaphor of decline: Elaine of Astolat and the downfall of Camelot - Gualberto Valverde, Rebeca (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen